Functional Outcomes and Quality of Life After Transanal Total Mesorectal Excision for Rectal Cancer: A Prospective Observational Study. Issue 1 (January 2022) - de Lacy, F. Borja; Turrado-Rodriguez, Víctor; Torroella, Alba; van Laarhoven, Jacqueline; Otero-Piñeiro, Ana; Almenara, Raúl; Lacima, Glòria; Castells, Antoni; Lacy, Antonio M.
Abstract : BACKGROUND: Few studies have addressed the functional impact after transanal total mesorectal excision. OBJECTIVE: This study aimed to evaluate function and health-related quality of life among patients with rectal cancer treated with transanal total mesorectal excision. DESIGN: Consecutive patients treated between 2016 and 2018 were selected. Their function and quality of life were studied preoperatively and at 3 and 12 months after surgery. SETTING: This is a prospective case series. PATIENTS: Patients were eligible if they had primary anastomosis, their diverting stoma had been reversed, and they did not have anastomotic leakage. Forty-five patients were finally included. A total of 31 (68.8%) and 32 patients (71.1%) completed the 3- and 12-month surveys. INTERVENTIONS: Standard transanal total mesorectal excision was performed. MAIN OUTCOME MEASURES: The primary end point was functional and quality-of-life outcomes using validated questionnaires. Secondary end points included values obtained with endoanal ultrasounds, anorectal manometries, and rectal sensation testing. RESULTS: Wexner and Low Anterior Resection Syndrome scores significantly increased 3 months after surgery but returned to baseline values at 12 months. The rate of "major low anterior resection syndrome" at the end of follow-up was 25.0% (+11.7% compared with baseline, p = 0.314). Sexual and urinary functions remained stable throughout the study, although a meaningful clinical improvement was detected in male sexual interest. Among quality-of-life domains, all deteriorations returned to baseline values 12 months after surgery, except worsening of flatulence symptoms, and improvement in insomnia and constipation. At 12 months, an expected decrease in the mean width of the internal sphincter, the anal resting pressure, and the tenesmus threshold volume was found. LIMITATIONS: This study was limited by its small sample size, the absence of a comparative group, and significant missing data in female sexual difficulty and in ultrasounds and manometries at 3 months. CONCLUSIONS: Patients undergoing transanal total mesorectal excision report acceptable quality-of-life and functional outcomes 12 months after surgery. See Video Abstract at http://links.lww.com/DCR/B541 . RESULTADOS FUNCIONALES Y CALIDAD DE VIDA DE LOS PACIENTES DESPUÉS DE LA ESCISIÓN MESORRECTAL TOTAL TRANSANAL PARA CÁNCER DE RECTO: UN ESTUDIO PROSPECTIVO OBSERVACIONAL: ANTECEDENTES: Pocos estudios han abordado el impacto funcional después de la escisión mesorrectal total transanal. OBJETIVO: Evaluar la función y la calidad de vida relacionada con la salud en pacientes con cáncer de recto tratados con escisión mesorrectal total transanal. DISEÑO: Se seleccionaron pacientes consecutivos tratados entre 2016 y 2018. Se estudió su función y calidad de vida, en la etapa preoperatoria, a los tres y doce meses postoperatorios. METODO: Serie de casos prospectivos. PACIENTES: Los pacientes eran incluidos en presencia de anastomosis primaria, cierre del estoma de derivación y en ausencia de fuga anastomótica. Finalmente se incluyeron cuarenta y cinco pacientes. Un total de 31 (68, 8%) y 32 pacientes (71, 1%) completaron las encuestas de tres y doce meses, respectivamente. INTERVENCIONES: Escisión mesorrectal total transanal estándar. PRINCIPALES MEDIDAS DE RESULTADO: Los criterio de evaluación principal fueron los resultados funcionales y de calidad de vida mediante cuestionarios previamente validados. Los criterios de evaluación secundarios incluyeron los valores obtenidos con ecografía endoanal, manometría anorrectal y prueba de sensibilidad rectal. RESULTADOS: La escala de Wexner y el síndrome de resección anterior baja aumentaron significativamente tres meses después de la cirugía, pero volvieron a los valores iniciales a los doce meses. La tasa de "síndrome de resección anterior inferior grave" al final del seguimiento fue del 25, 0% (+ 11, 7% en comparación con el valor inicial, p = 0, 314). La función sexual y urinaria se mantuvo estable durante todo el estudio, aunque se detectó una mejora clínica significativa en la libido masculina. Entre los criterios que evalúan la calidad de vida, todas las alteraciones en la misma volvieron a los valores iniciales, doce meses después de la cirugía, excepto el aumento de flatulencia, la mejoría del insomnio y el estreñimiento. A los doce meses, se encontró una disminución esperada en el grosor medio del esfínter interno, la presión anal en reposo y el volumen umbral para la presencia de tenesmo. LIMITACIONES: Tamaño de muestra limitado, ausencia de un grupo comparativo, falta significativa de datos para identificar la dificultad para la actividad sexual femenina y el efectuar ecografía y manometría a los tres meses. CONCLUSIONES: Los pacientes sometidos a escisión mesorrectal total transanal refieren una calidad de vida y resultados funcionales aceptables a los doce meses después de la cirugía. Consulte Video Resumen en http://links.lww.com/DCR/B541 . Abstract : Supplemental Digital Content is available in the text.